Study on the stability of particle packing structure based on cells - Hua, Yunsong; Xin, Yujiao; Dai, Hongyang; Yang, Hui; Chi, Zhipeng; Li, Ran (Frontiers in Physics, 2022)
The macroscopic mechanical property and the stability of granular mechanics system are determined by packing structure. Cells play a fundamental role in granular statistical mechanics and thus cells were utilized in this paper to research the packing structure of disk particles and gear particles in a two-dimensional cubic container. The probability distribution of cell order satisfies the exponential function distribution and is independent of intergranular friction, the size of system and vibration. Furthermore, it is observed that friction and system size are the key factors affecting the stability of particle packing structure. Significantly, the relationship between volume fraction and packing structure of disk particles is established under vibration. The experimental results reveal the characteristics of ordered packing structure of disordered particle system in mesoscale and provide data reference for perfecting the theory of particle mechanics.